Answer
y - 40 = -2 (x - 2)
We can simplify this
y - 40 = -2x + 4
y = -2x + 4 + 40
y = -2x + 44
Step-by-step explanation
The general form of the equation in point-slope form is
y - y₁ = m (x - x₁)
where
y = y-coordinate of a point on the line.
y₁ = This refers to the y-coordinate of a given point on the line
m = slope of the line.
x = x-coordinate of the point on the line whose y-coordinate is y.
x₁ = x-coordinate of the given point on the line
We need to calculate the slope and to use one of the points given as (x₁, y₁)
For a straight line, the slope of the line can be obtained when the coordinates of two points on the line are known. If the coordinates are (x₁, y₁) and (x₂, y₂), the slope is given as
![Slope=m=\frac{Change\text{ in y}}{Change\text{ in x}}=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2023/formulas/mathematics/college/2spudbjlkh14f60l20sveubtri0s31xnrj.png)
(x₁, y₁) and (x₂, y₂) are (2, 40) and (20, 4)
![\text{Slope = }(4-40)/(20-2)=(-36)/(18)=-2](https://img.qammunity.org/2023/formulas/mathematics/college/9z35f2qt47w7xfn2ty5fyoz2qd3sanbadg.png)
Slope = m = -2
(x₁, y₁) = (2, 40)
x₁ = 2, y₁ = 40
y - y₁ = m (x - x₁)
y - 40 = -2 (x - 2)
We can simplify this
y - 40 = -2x + 4
y = -2x + 4 + 40
y = -2x + 44
Hope this Helps!!!